2014
DOI: 10.12809/hkmj134027
|View full text |Cite
|
Sign up to set email alerts
|

Current practices, attitudes, and perceived barriers for treating smokers by Hong Kong dentists

Abstract: Dentists in Hong Kong generally had positive attitudes towards smoking cessation advice. The dental team is in a very good position to help smokers quit. However, training and guidelines designed specifically for dental teams are paramount to overcome barriers in delivering smoking cessation advice by dental professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…A study in Hong Kong showed that dentists practicing in government sectors and those who have undergone training in tobacco cessation were more likely to enquire about their patients' smoking status. Thus, appropriately trained dentists were 14 times more familiar with contacting local smoking cessation agencies and 8 times more likely to provide advice for smoking cessation to their patients (15). This study reflected the need for both didactic and clinical training in counselling skills in the undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…A study in Hong Kong showed that dentists practicing in government sectors and those who have undergone training in tobacco cessation were more likely to enquire about their patients' smoking status. Thus, appropriately trained dentists were 14 times more familiar with contacting local smoking cessation agencies and 8 times more likely to provide advice for smoking cessation to their patients (15). This study reflected the need for both didactic and clinical training in counselling skills in the undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 80%
“…Attitude of dentists in providing tobacco use cessation advice also depends on many background factors such as past experiences with counselling, and interest and rewards in practice and training (13,14). In a study among Hong Kong dentists, 89% strongly agreed that dentists play an important role in delivering tobacco cessation advice (15). Likewise, 80.6% of dentists in Saudi Arabia agreed about the importance of providing tobacco cessation counselling and only 9% of them disagreed (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-professional characteristics of dentists were found to influence prescribing practices 9 , and their age, in particular, was found to affect their attitude towards tobacco cessation 10 . Another important aspect of tobacco cessation in the dental setting is the smoking status of dentists.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent survey of Hong Kong dentists found that only half of them provided such advice routinely; the main reported barriers being lack of training, lack of confidence, and fear of damaging relationship with their patients. 6 Furthermore, since many individuals visit dentists regularly for checkups, it makes good sense to use these opportunities to look out for the oral manifestations of systemic diseases in them, give appropriate health advice, and make referrals to doctors as necessary. 7,8 The need for more collaboration between dental and medical professionals to provide better patient health care services is not one-sided.…”
Section: Enhancing Health Care Services Through Close Collaboration Bmentioning
confidence: 99%